AN OVERVIEW OF OBESITY RISK FACTORS IN THE STUDENTS OF POLTEKKES KEMENKES TASIKMALAYA - Asep AS Hidayat; Tri Kusuma A. Puruhita; Dewi Aryanti; Sofia Februanti (Universitas Respati Yogyakarta, 2022)
The risk factors of adolescent obesity are caused by macronutrient intake, diet and eating habits, physical activity, genetics, knowledge, attitudes, and psychological. This study aimed to determine obesity risk factors for students of Poltekkes Kemenkes Tasikmalaya. This descriptive research studied on 100 students. Obesity is determined by BMI, while body fat composition is determined by the bioimpedance analysis method. Intake and diet were measured through interviews, using a 24-hour recall form, an FFQ questionnaire, and a PGS instrument. Physical activity was measured using the IPAQ form. Knowledge and attitudes are determined by interviews, using knowledge and attitudes instruments. The data were analyzed descriptively. Food intake data were processed using Nutrisurvey 2007 for Windows. BMI showed 64% belong to the obesity 1. The average of body weight was 73.96 Kg ± 11.89. The incidence of obesity occurs a lot during adolescence and college (70%), 48% have obese parents, and 42% have obese siblings. The average body fat was 32.84% ± 5.59 and the average visceral fat was 9.57 ± 4.72. Fat and carbohydrate intake and energy were 100% less than DV, while protein intake was 85% less than DV. The diet of carbohydrate and vegetable sources was less than normal, while protein and fruit sources tend to be normal. Physical activity was low with 46%. The average knowledge score was 75.1% ± 12.98, and the average attitude score was 78.2% ± 14.17. Keywords: Physical Activity; Intake; Obesity; Knowledge; Diet